2023
DOI: 10.1007/s12469-022-00312-5
|View full text |Cite
|
Sign up to set email alerts
|

A simulation-based optimization approach for designing transit networks

Abstract: Public transport network design deals with finding efficient network solution(s) from a set of alternatives that best satisfies the often-conflicting objectives of stakeholders like passengers and operators. This work presents a simulation-based optimization (SBO) model for designing public transport networks. The work’s novelty is in developing such a network design model that fully accounts for the stochastic behavior of commuters on the transit network. The SBO discipline solves decision-based problems like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Operation costs and travel costs were minimized under the framework of a mixed-integer nonlinear programming problem using a branch and bound algorithm [84]. Nnene et al presented a simulation-based optimization for designing public transport networks [85]. An activity-based simulation was used and it was shown by the example of Cape Town (South Africa) that efficient networks can be created [85].…”
Section: Public Transportation Planning Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Operation costs and travel costs were minimized under the framework of a mixed-integer nonlinear programming problem using a branch and bound algorithm [84]. Nnene et al presented a simulation-based optimization for designing public transport networks [85]. An activity-based simulation was used and it was shown by the example of Cape Town (South Africa) that efficient networks can be created [85].…”
Section: Public Transportation Planning Processmentioning
confidence: 99%
“…Nnene et al presented a simulation-based optimization for designing public transport networks [85]. An activity-based simulation was used and it was shown by the example of Cape Town (South Africa) that efficient networks can be created [85]. The study by Yoon and Chow suggested an artificial intelligence-driven algorithm to combine transit network design with optimal learning [86].…”
Section: Public Transportation Planning Processmentioning
confidence: 99%
“…These can be seen through the development of integrated transport systems in countries like South Africa, Nigeria, Tanzania, India, Brazil and Vietnam [24,42]. In South Africa, the development of a bus rapid transit (BRT) system was meant to cater to the urban poor's public transport needs and provide sustainable mobility options [43]. Likewise, the Dakar Bus Rapid Transit Pilot Project in Senegal approved in 2017 is currently being implemented and is envisaged to carry approximately 300,000 passengers per day while reducing their travel times from 95 to 45 min [44].…”
Section: Introductionmentioning
confidence: 99%
“…The decision-makers may require proper methods to help them, especially when dealing with complex systems where the objectives under analysis conflict with themselves, such as in multi-objective complex problems [ 1]. Some of these methods include the use of optimization and simulation to find solutions that are suitable for decision-makers [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Ramirez et al [ 4] used simulation and optimization to minimize oil and gas industry costs and time. Nnene et al [ 2] used simulation and optimization to solve a transit network design problem, in which simulation evaluates alternative network solutions by simulating travel demand on them while a multi-objective optimization algorithm searches for efficient network solutions. Simulation-optimization is thus a powerful decision-making tool that has the ability to capture intricate relationships and interactions among several entities in a real-world complex system and identify the best design point [ 6].…”
Section: Introductionmentioning
confidence: 99%